NANOCHITOSAN AND DENTAL BIOFILMS – A REVIEW - NATHASHA M, MAYMA; DURAISAMY, SANGEETHA; KANNAN, RAVI (International Journal of Psychosocial Rehabilitation, 2024)
Dental biofilms harbor harmful microorganisms that causes dental caries and periodontal diseases.Chitosan is a naturally occurring polysaccharide with antimicrobial properties against a widespectrum of bacteria and fungus. Chitosan nanoparticles possess unique physicochemicalcharacteristics, when utilized properly can be used to prevent the formation or reduction of plaquebio mass by acting against the microbes present in the plaque and disruption of mature biofilm.